Nitroxyl Delivered by Angeli’s Salt Causes Short‐Lasting Activation Followed by Long‐Lasting Deactivation of Meningeal Afferents in Models of Headache Generation - Stöckl, Stephanie K.; De Col, Roberto; Filipovic, Milos R.; Meßlinger, Karl (International Journal of Molecular Sciences, 2022)
The role of TRPA1 receptor channels in meningeal nociception underlying the generation of headaches is still unclear. Activating as well as inhibitory effects of TRPA1 agonists have been reported in animal models of headache. The aim of the present study was to clarify the effect of the TRPA1 agonist nitroxyl (HNO) delivered by Angeli’s salt in two rodent models of meningeal noci-ception. Single fibre recordings were performed using half‐skull preparations of mice (C57BL/6) in vitro. Angeli’s salt solution (AS, 300 μM) caused short‐lasting vigorous increases in neuronal activity of primary meningeal afferents, followed by deactivation and desensitisation. These effects were similar in TRPA1 knockout and even more pronounced in TRPA1/TRPV1 double‐knockout mice in comparison to wild‐type mice. The activity of spinal trigeminal neurons with afferent input from the dura mater was recorded in vivo in anesthetised rats. AS (300 μM) or the TRPA1 agonist acrolein (100 and 300 μM) was applied to the exposed dura mater. AS caused no significant changes in spontaneous activity, while the mechanically evoked activity was reduced after acrolein application. These results do not confirm the assumption that activation of trigeminal TRPA1 receptor channels triggers the generation of headaches or contributes to its aggravation. Instead, there is evidence that TRPA1 activation may have an inhibitory function in the nociceptive trigeminal system.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Acrolein; Headache; Mouse; Nitroxyl; Primary meningeal afferents; Rat; Spinal trigeminal neu-rons; Trigeminal nociception; TRPA1 receptors